The therapeutic effect of PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres combined with magnetic fluid hyperthermia on hepatoma - Zhang, Hao; Li, Suping; Chen, Fei; Ma, Xingming; Liu, Mingying (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is one of the most prevalent and deadly malignant tumors with serious clinical and socioeconomic consequences. Although gene therapy holds great promise in the treatment of hepatoma, its clinical applications are hindered by uncontrolled gene transmission and transcription. In order to develop an efficient, targeted and safe tumor treatment system, we have constructed an immune gene delivery system combines gene therapy with hepatoma hyperthermia by using magnetic nanoparticles (MNPs) as carriers. The immune gene was induced by radiation and enhanced by hypoxia. MNPs could raise the temperature to optimal range for tumor hyperthermia under the influence of an alternating magnetic field (AMF). The therapeutic effect of PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres combined with magnetic fluid hyperthermia on hepatoma were evaluated in vitro and in vivo. The results indicated the successful construction of the radiation-induced plasmid and demonstrated that the hypoxia enhancer could augment the expression of INFγ in a hypoxia environment. Gene therapy combined with magnetic fluid hyperthermia (MFH) has exhibited excellent outcomes in both cell and animal studies. Our experiments demonstrated that the PEI-Fe3O4/pYr-ads-8-5HRE-cfosp-IFNG albumin nanospheres system is a comprehensive treatment method for hepatoma, which can effectively combine immune genre therapy with hyperthermia.